2013
DOI: 10.1007/s10532-013-9674-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioaugmentation on enhanced reductive dechlorination of 1,1,1-trichloroethane in groundwater: a comparison of three sites

Abstract: Microcosm studies investigated the effects of bioaugmentation with a mixed Dehalococcoides (Dhc)/Dehalobacter (Dhb) culture on biological enhanced reductive dechlorination for treatment of 1,1,1-trichloroethane (TCA) and chloroethenes in groundwater at three Danish sites. Microcosms were amended with lactate as electron donor and monitored over 600 days. Experimental variables included bioaugmentation, TCA concentration, and presence/absence of chloroethenes. Bioaugmented microcosms received a mixture of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Lactate-amended microcosms showed the shortest lag-phase (i.e., time prior to the onset of dechlorination) and the highest initial dechlorination rate; similar results were obtained by Aulenta et al (2005b) . As in other studies, highly chlorinated parent compounds are dechlorinated more quickly than their lesser chlorinated daughter products ( Scheutz et al, 2014 ; Miura et al, 2015 ) The microcosms amended with lactate and butyrate showed a complete dechlorination, but the lactate seems to be the best electron donor. The adding of digester sludge, with a strictly anaerobic microbial community, led to a quicker dechlorinating activity compared to the amended treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Lactate-amended microcosms showed the shortest lag-phase (i.e., time prior to the onset of dechlorination) and the highest initial dechlorination rate; similar results were obtained by Aulenta et al (2005b) . As in other studies, highly chlorinated parent compounds are dechlorinated more quickly than their lesser chlorinated daughter products ( Scheutz et al, 2014 ; Miura et al, 2015 ) The microcosms amended with lactate and butyrate showed a complete dechlorination, but the lactate seems to be the best electron donor. The adding of digester sludge, with a strictly anaerobic microbial community, led to a quicker dechlorinating activity compared to the amended treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Degradation of 1,1,1-TCA in all biotic microcosms including the biotic control has been documented by the isotope data, and mass and isotope balance have confirmed that 1,1-DCA is not a The degradation rates for 1,1,1-TCA in biotic control and stimulated microcosms and initially in bioaugmented microcosms (0.0023-0.0056 d À1 ) are relatively low compared to biodegradation rates (Scheutz et al, 2013). However, significant carbon isotope enrichment factors (À10‰ to À14‰) are observed.…”
Section: Degradation Rates and Enrichment Factorsmentioning
confidence: 81%
“…Elsner and Hofstetter (2011) proposed an abiotic pathway for 1,1,1-TCA (via organochloride radical and/or carbanion) with primarily non-chlorinated degradation products (including acetaldehyde and ethane) analogue to the abiotic pathway for carbon tetrachloride (CTET) degradation (to carbon monoxide and formate or carbon disulfide) by pyrite and FeS observed by Kriegman-King and Reinhard (1994) and Devlin and Müller (1999), respectively, and reviewed by Elsner and Hofstetter (2011). In a treatability study for 1,1,1-TCA bioremediation for 3 clay till sites in Denmark by Scheutz et al (2013) it was inferred from degradation results and mass balance determinations that an alternate biologically mediated 1,1,1-TCA degradation pathway (without accumulation of 1,1-DCA and CA) contributed to 1,1,1-TCA loss in intrinsic controls.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that biofilms formed by AN-1 added in GCWs greatly improved remediation of aniline. It as a case study shows the advantage of such an in situ remediation strategy: (a) Biofilms in GCWs can biodegrade the remaining low-volatile contaminants which cannot be removed by aeration; (b) Biodegradation mainly occurs in the well and it is easy to be monitored and controlled; (c) The carriers with biofilms can be replaced conveniently to maintain efficiency; (d) This system can disperse planktonic degrading bacteria among the area of circle radius by hydraulic actions, which is similar to bioaugmentation, contributing to enhance the remediation efficiency (Lyon and Vogel 2013;Scheutz et al 2014). However, due to the complexity of contaminated sites, GCWs should be widely focused on and further investigated.…”
Section: Degradation Of Aniline In a Laboratory-scale Gcw Systemmentioning
confidence: 99%